Burner - Greaney, Mark (Greaney, Mark. Gray Man novel ;, 2023)
"In the latest thrilling novel in the #1 New York Times bestselling Gray Man series, Court Gentry is sent on a mission by a person he doesn't trust to snatch a target he can't stand from the clutches of Russian assassins he can't defeat... and those are the upsides of the job. Alex Velesky is in a world of trouble. He has the key that can unlock the truth behind a web of illicit payments the Russians have spread around the globe. The money is used to subvert governments, pay off politicians and bankroll terrorist groups-among other things. Incredibly powerful forces will do anything to keep this particular secret from getting out. But the only man who can put the information together and get it out to the world is 4000 miles away in New York City. There's no way a Swiss banker like Velesky can hope to stay ahead of the killers on his trail that long. Lucky for him, he's got an ace up his sleeve. Zoya Zakharova, former Russian intelligence officer, former CIA agent and the Gray Man's current lover is determined to get the information and its courier safely to its destination. What she doesn't know is that there is one particularly dangerous force standing in her path--Court Gentry. In the past, he and Zoya have always worked together, but even two people who have spent their lives in the shadows can lose themselves in the dark"--